Nutritional Content of Bone Flour Made from Plecos Fish Pterygoplichthys pardalis from the Ciliwung River, Indonesia - Handhini Dwi Putri; Dewi Elfidasari; Haninah Haninah; Irawan Sugoro (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Pterygoplichthys pardalis bones that are thrown into the river is one source of pollutants in the Ciliwung River. P. pardalis bones have a high calcium content, they can be used as an alternative raw material for flour. The purpose of this study was to analyze the nutritional content of P. pardalis bone flour from the Ciliwung River. The research method used was a proximate analysis consisting of moisture, ash, fat, protein, and carbohydrates content analyses. Proximate analysis results showed that the P. pardalis bone plus head flour contained 3% moisture, 35% ash, 34% protein, 23% fat, and 5% carbohydrate. P. pardalis body bone flour contained 4% water, 37% ash, 37% protein, 19% fat, and 3% carbohydrate. Based on the proximate analysis results, P. pardalis bone flours did not met the national standard of SNI 2013 fish flour for quality I, II, and III. Until now, there has been no research that explain the nutritional content of bone flour of P. pardalis from Ciliwung River. This research provides information on the nutritional content of P. pardalis flour. Data obtained from the results of this study can be the basis for consideration in utilizing and processing P.pardalis from the Jakarta Ciliwung River.